KAJIAN FILOSOFIS PENGEMBANGAN SPESIALISASI MAHASISWA VOKASI OTOMOTIF MELALUI TEORI PERKEMBANGAN KARIER SUPER - Maulana, Fajar; Refdinal, Refdinal; Abdullah, Rijal; Mardizal, Jonni (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The rapid transformation of the automotive industry towards digitalization and electric vehicles requires vocational graduates to have new competencies as well as a clear career path based on self-concept. However, students' unpreparedness in determining their specialization and the mismatch between their competencies and the needs of the EV industry make the development of a career guidance model even more important. This study aims to analyze the relevance of Super's career development theory in specialization guidance in the Automotive Engineering Vocational Program and to formulate a Self-concept-based career guidance model that is adaptive to the demands of electric vehicle technology. For this purpose, an analytical-philosophical literature review was conducted, examining 35 scientific articles and primary literature on Super's theory. The results show that the stages of career exploration, crystallization, specification, and implementation in Super's theory are in line with the process of forming EV competencies such as BMS, HV safety, electric motors, and digital diagnostics. Another important finding is that technical self-concept is formed through direct learning experiences and guided reflection, so career guidance needs to integrate self-assessment, exploration, workshops, and field experience. The study concludes that Super's theory is relevant as a foundation for vocational career guidance in the era of electrification and recommends the development of a curriculum that emphasizes career exploration and empirical research to test the effectiveness of the model.Keyword: Vocational Career; Super Theory; Electric Vehicles; Self-Concept; Career Guidance.Abstrak: Transformasi pesat industri otomotif menuju digitalisasi dan kendaraan listrik menuntut lulusan vokasi memiliki kompetensi baru sekaligus kejelasan arah karier yang berbasis Self-concept. Fenomena ketidaksiapan mahasiswa dalam menentukan spesialisasi serta ketidaksesuaian kompetensi dengan kebutuhan industri EV menjadikan pengembangan model bimbingan karier semakin penting. Penelitian ini bertujuan menganalisis relevansi teori perkembangan karier Super dalam pembimbingan spesialisasi pada Program Vokasi Teknik Otomotif serta merumuskan model bimbingan karier berbasis Self-concept yang adaptif terhadap tuntutan teknologi kendaraan listrik. Metode penelitian menggunakan kajian pustaka analitik-filosofis dengan menelaah 35 artikel ilmiah dan literatur primer teori Super. Hasil penelitian menunjukkan bahwa tahapan eksplorasi, kristalisasi, spesifikasi, dan implementasi karier pada teori Super selaras dengan proses pembentukan kompetensi EV seperti BMS, HV safety, motor listrik, dan diagnostik digital. Temuan penting lainnya adalah bahwa Self-concept teknis terbentuk melalui pengalaman belajar langsung dan refleksi terarah, sehingga bimbingan karier perlu mengintegrasikan asesmen diri, eksplorasi, workshop, dan pengalaman lapangan. Penelitian menyimpulkan bahwa teori Super relevan sebagai landasan pembimbingan karier vokasional pada era elektrifikasi dan merekomendasikan pengembangan kurikulum yang menekankan eksplorasi karier serta penelitian empiris untuk menguji efektivitas model yang diusulkan.Kata kunci: Karier Vokasional; Teori Super; Kendaraan Listrik; Self-Concept; Bimbingan Karier.